Determination of Fatigue Crack Length of Rail Steels: A Recent Approach - Gupta, N.; Shahwaz, Md.; Singh, B.; Ahmad, Saif Nawaz; Priyadarshi, Neeraj; Bhoi, A. K. (Recent Progress in Science and Technology Vol. 1, 2023)
The purpose of this work is to discuss principle of fatigue crack length behaviour. The fatigue testing method was carried out at the Physical Metallurgy Lab of the Research and Development Centre for Iron and Steel (RDCIS), SAIL, Ranchi, in order to determine the utilisation of fatigue properties of RAIL STEELS. Samples were produced by SAIL at Bhilai Steel Plant. The hardness, metallographic, and EDS tests were performed in addition to the fatigue test. Following the fatigue test, the fractured surface was examined under a scanning electron microscope (SEM) to determine the mode of fracture and any stress raisers, such as inclusions or other imperfections.